2021
DOI: 10.3389/fimmu.2021.698894
|View full text |Cite|
|
Sign up to set email alerts
|

Myeloid-Derived Suppressor Cells Alleviate Renal Fibrosis Progression via Regulation of CCL5-CCR5 Axis

Abstract: BackgroundRenal fibrosis is inevitable in all progressive chronic kidney diseases (CKDs) and represents a serious public health problem. Immune factors contribute to the progression of renal fibrosis. Thus, it is very possible that immunosuppression cells, such as myeloid-derived suppressor cells (MDSCs), could bring benefits to renal fibrosis. Herein, this study investigated the antifibrotic and reno-protective effect of MDSCs and the possible mechanisms.MethodsMurine and cell models of unilateral ureter obst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…The potential function of the above genes has been reported in renal fibrosis. For instance, the CCL5-CCR5 axis and the TGF-1/Smad/Snail signaling pathways were inhibited by inducing myeloid-derived suppressor cells in vitro and in vivo, and both methods reduced kidney fibrosis [ 30 ]. Smad4 deacetylation and inhibition of MMP7 expression by upregulated SIRT1 in RSV reduced kidney damage and fibrosis, which was related to the upregulation of SIRT1 by RSV [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The potential function of the above genes has been reported in renal fibrosis. For instance, the CCL5-CCR5 axis and the TGF-1/Smad/Snail signaling pathways were inhibited by inducing myeloid-derived suppressor cells in vitro and in vivo, and both methods reduced kidney fibrosis [ 30 ]. Smad4 deacetylation and inhibition of MMP7 expression by upregulated SIRT1 in RSV reduced kidney damage and fibrosis, which was related to the upregulation of SIRT1 by RSV [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…TGF‐β1 binds to its receptor, prompting phosphorylation of SMAD2 and SMAD3, forming the SMAD complex by binding to SMAD4, driving Snail expression and promoting epithelial‐mesenchymal transition and fibrosis 154–156 . Although it is unclear whether MDSCs ameliorate fibrosis of DN by this way, in unilateral ureter obstruction mice model, bone marrow‐induced MDSCs significantly inhibit the TGF‐β1/SMAD/Snail pathway and thus alleviate renal fibrosis progression 157 …”
Section: Mdscsmentioning
confidence: 99%
“…[154][155][156] Although it is unclear whether MDSCs ameliorate fibrosis of DN by this way, in unilateral ureter obstruction mice model, bone marrow-induced MDSCs significantly inhibit the TGF-β1/SMAD/Snail pathway and thus alleviate renal fibrosis progression. 157…”
Section: Characteristics Of Mdscs In Diabetic Conditionmentioning
confidence: 99%
“…In contrast, increased renal infiltration of MDSC upon granulocyte colony-stimulating factor (G-CSF) administration improved renal function after IRI and attenuated acute tissue injury as well as chronic renal fibrosis ( 68 , 69 ). In addition, further mechanistic studies have shown that renal fibrosis can be alleviated by MDSC through CCL5-CCR-5 axis regulation and TGF-β1/Smad/Snail signaling pathway inhibition ( 70 ).…”
Section: The Role Of Mdsc In Ischemia–reperfusion Injurymentioning
confidence: 99%